2015
DOI: 10.1021/jacs.5b07895
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Reaction Course in O-Glycosidation with O-Glycosyl Trichloroacetimidates as Glycosyl Donors and Lewis Acidic Metal Salts as Catalyst: Acid–Base Catalysis with Gold Chloride-Glycosyl Acceptor Adducts

Abstract: Gold(III) chloride as catalyst for O-glycosyl trichloroacetimidate activation revealed low affinity to the glycosyl donor but high affinity to the hydroxy group of the acceptor alcohol moiety, thus leading to catalyst-acceptor adduct formation. Charge separation in this adduct, increasing the proton acidity and the oxygen nucleophilicity, permits donor activation and concomitant acceptor transfer in a hydrogen-bond mediated S(N)2-type transition state. Hence, the sequential binding between acceptor and catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 42 publications
4
79
1
1
Order By: Relevance
“…It is pleasing to note that on reaction with partially protected acceptor 22 with glycosyl donors 1α and 7α under the optimized conditions lead to the regioisomeric products 23 and 24 [4647] in moderate yields with good selectivity (Scheme 2). …”
Section: Resultsmentioning
confidence: 99%
“…It is pleasing to note that on reaction with partially protected acceptor 22 with glycosyl donors 1α and 7α under the optimized conditions lead to the regioisomeric products 23 and 24 [4647] in moderate yields with good selectivity (Scheme 2). …”
Section: Resultsmentioning
confidence: 99%
“…Next, we set out to investigate the β‐selective glycosylation with the separately synthesized epoxy alcohol 6 (Scheme ). Various glycosyl donors and activation conditions were examined without success (glycosylfluoride, thioglycoside, phosphoramidate, phosphite ester, trichloroacetimidate,). Extensive experimentation revealed that the combination of 14 and Ph 3 CB(C 6 F 5 ) 4 in a n PrCN/CH 2 Cl 2 mixture resulted in the disaccharide β‐ 15 in 81 % yield with 4.3 to 1 selectivity in favor of the β diastereoisomer.…”
Section: Figurementioning
confidence: 99%
“…Notably, in this case, high β‐ stereoselectivity was obtained. Recently, further investigation into gold catalysts by Peng and Schmidt has demonstrated the successful synthesis of glycosides with trichloroacetimidate donors via an intramolecular dual catalysis pathway, where AuCl 3 acted as an initiator for the formation of catalyst–acceptor adducts. Interestingly, they obtained high β ‐stereoselective products even with the use of armed glycoside donors.…”
Section: Glycosylationsmentioning
confidence: 99%